Possible effects of hormonal contraceptives on human and baboon mitosis chromosomes - Pinto, Maximina Rodrigues (My University, 1983)
Hormonal - contraceptives - ' the pill ' as it is known to the general public - are among the most universally used drugs in our contemporary world. Daily millions of health young women are taking the ' pill ' for a purpose other than the control of disease
A Thesis submitted to the Faculty of Medicine University of the Witwatersrand,, Johannesburg, for a Degree of Doctor of Philosophy
Keywords: Contraceptives, Oral, Hormonal; Chromosomes; Lymphocytes